Caracterização e conservação pós-colheita de Camu-camu (Myrciaria dubia (Kunth) Mc Vaugh) - Grigio, Maria Luiza (2013)
The camu-camu tree (Myrciaria dubia (Kunth) Mc Vaugh) is fruit-bearing tree belonging to the family Myrtaceae. It possesses economic potential for being concerned with the fruit of greatest amount of vitamin C, coming to reach 6.112 mg of ascorbic acid per 100 g-1 of pulp. It was aimed through the present wok to characterize the camu-camu fruit by detecting the best harvest date for the fruit as well as to test post-harvest and storage technologies in their conservation. Two experiments were conducted. The first one aimed at the determination of the harvest date where the fruits were collected at three different ripening stages (unripe, semi- ripe and ripe) and stored for eight days. In the second one, packages and storage temperatures constituting the following treatments were tested: T1 (with no package at room temperature, 22 °C); T2 (with no package at 15 °C); T3 (with no package at 20 °C); T4 (PET at room temperature, 22 °C); T5 (PET at 15 °C); T6 (PET at 20 °C); T7 (PVC at room temperature, 22 °C); T8 (PVC at 15 °C); and T9 (PVC at 20 °C). The designs utilized were completely randomized in factorial arrangement. The fruit were analyzed daily as to: the loss of fresh mass, pH, contents of soluble solids (SS), titrable acidity (TA), ascorbic acid (AA), total vitamin C, carotenoids, anthocyanins, chlorophylls A e B, flavonoids and total phenolic compounds as well as the antioxidant activity (FRAP and DPPH) and the maturation index (SS/TA). At the semi- ripe stage, there was a greater conservation of the quality attributes (SS, TA and less mass loss) as well as of the ascorbic acid content and of the antioxidant activity (FRAP). The pigments carotenoides, flavonoids and anthocyanins as well as the content of vitamin C presented higher amounts in the fruit collected matures; that stage being regarded as the appropriate for the extraction of those functional biocompounds. That harvest date also corresponded to the highest average content of total phenolics and of the antioxidant activity (DPPH). So, the best harvest date for the extraction of both pigments and antioxidant biocompounds of camu-camu is the ripe stage. When the intention is obtaining longest shelf-life, the best harvest date is the semi-ripe, for conserving the qualitative attributes for longer. In the post-harvest storage of the camu-camu, it follows that the best conservation of the qualitative attributes and the best conservation of the pigments and antioxidant biocompounds occurred when the fruit were stored at 15 °C jointly with the expanded polystyrene tray covered with PVC film.